Crowd modelling behaviour based on modified microscopic models in panic situation - Sharbini, Hamizan (2010)
There are many models lies under microscopic level that can serve as a basis to simulate crowd in more realistic and believable. The purpose of crowd simulation is to model the motions of objects within a specific environment. Applications of crowd simulation are numerous such as in computer science that includes study of crowd behaviour under different environmental conditions like panic situation. Therefore, this project will focus on analysis via available literature and to produce more realistic simulation based the microscopic models, namely Social Force Model (SF) that can reproduce individual and collective behaviours observed in real emergency evacuation situation. The modification of the model element will only pertain to crowd movement behaviour modelling in order to find an exit from a room in panic situation. This also incorporates simple visualization such that it has only a single point per object, whereby the people in crowd will be modeled using particle.